Current adhesive systems and main challenges in adhesion: narrative review (Research, Society and Development, 2021)
Adhesion is the force that allows substances or substrates of different compositions to remain united as they are in close contact. Dental substrates have very different characteristics and are complex to understand when submitted to adhesive systems, which is the main challenge that dentists have faced in restorative dentistry. Considering that there is a great deficiency in the professional's knowledge regarding the techniques, indications and properties of dental adhesives, the objective of this narrative literature review was to clarify the classification and current aspects of adhesive systems, in addition to pointing out the main challenges that the clinician can face come across during the process of adhesion to dental tissues. Currently, adhesive systems are classified as conventional, self-etching and universal. Factors such as selective enamel conditioning when using self-etching systems and the use of adhesive systems that contain functional monomers that favor chemical adhesion to dentin substrate are interesting for increasing bond strength. The literature points to factors that negatively impact bond strength, such as the use of hemostatic solutions, patients who received radiotherapy, carious dentin and sclerotic dentin.